Mismatch Amplification Mutation Assays of Chikungunya Virus and O'nyong-Nyong Virus; A Simple and Reliable Method for Surveillance and Identification of Emerging Alphaviruses - Lwande, Olivia Wesula; Luande, Verah Nafula; Pereira de Freitas, Amanda; Tajedin, Leila; Ahlm, Clas; Näslund, Jonas; Evander, Magnus; Bucht, Göran (Frontiers in Virology, 2022)
Background The mosquito-borne alphaviruses chikungunya virus (CHIKV) and o'nyong-nyong virus (ONNV) are closely related Alphaviruses that belong to the Semliki forest virus serocomplex. The two viruses are associated with large outbreaks with significant morbidity. However, they are transmitted by different mosquito vectors and accordingly need different prevention strategies. The viruses are difficult to distinguish clinically and there is a lack of sensitive and specific assays that can discriminate between CHIKV and ONNV. Therefore, there is a need for new methods that may be able to determine the true burden of the diseases caused by these viruses, especially in resource-poor settings. Method To distinguish between CHIKV and ONNV, we designed and optimized two genetic methods, melt analysis of mismatch amplification mutation assay (Melt-MAMA) and agarose gel-based mismatch amplification mutation assay (Agarose-MAMA). The identification was based on single nucleotide polymorphisms using two competing forward primers and a common reverse primer that targeted selected sites in the envelope genes (E1 and E2). A specific shift in the melting point and mobility on agarose gels was obtained by tailing one of the two competing primers with a G/C-rich stretch of nucleotides. Results The melting point analyses by real-time polymerase chain reaction (qPCR Melt-MAMA) or gel-shift assay (Agarose-MAMA assay) for CHIKV and ONNV were found to be reproducible and the sensitivity of the two assays was estimated at under 100 template copies/reaction. Furthermore, no cross-reactivity with related viruses of the same serocomplex such as Mayaro virus, Ross River virus or Semliki forest virus was detected, or with other viruses such as Sindbis virus (Alphavirus), West Nile virus, dengue virus (Flavivirus), Inkoo virus and Tahyna virus (Orthobunyavirus). The results from the two assays were comparable when the obtained amplicons were analyzed by Melt-MAMA or by Agarose-MAMA. Conclusion Herein we present reliable and robust methods that can discriminate between CHIKV and ONNV. These methods can be used in well-equipped laboratories and basic clinical settings (e.g., in developing countries), as well as in field situations. The approach may also be applicable in the distinction of other closely-related mosquito-borne viruses that belong to the same serogroup.